Study Of Chemical Properties Of Soil On Gambir (Uncarıa Gambir Roxb) Land Based On Slope İn Nagari Siguntur, Koto XI Tarusan district, Pesisir Selatan regency, Indonesia - Kenti, Helda; Rasyidin, Azwar; Gusnidar, Gusnidar (WBS Laboratory, 2025)
Gambier plants (Uncaria gambir.Roxb) are the main plantation commodity in West Sumatra. However, cultivating gambier on steep slopes can cause changes in soil chemical properties. This research aims to examine the chemical properties of soil on gambier land based on slope class in Nagari Siguntur. This research was carried out from June to December 2022. The method used was a survey method with the Purposive Random Sampling technique. Soil samples taken were soil samples on 3 slopes and forest as a control (45%) at a depth of 0-30 cm with 3 replications. The analysis results show the soil pH value is between 3.98–4.47 with very acid criteria. Soil C-Organic content is between 0.86%-1.76% with very low to low criteria. The N-Total content is between 0.26%-0.32% with medium criteria. The P-Available content is between 2.15 ppm-13.54 ppm with very low to low criteria. CEC with a value of 14.39-17.02 cmol/kg with low to moderate criteria. And the exchangeable cations in gambier land are classified as very low criteria.